2012
DOI: 10.1007/s13238-012-2025-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipid homeostasis and the formation of macrophage-derived foam cells in atherosclerosis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 73 publications
(75 reference statements)
1
107
0
1
Order By: Relevance
“…2A) and 20 differentially regulated KEGG pathways; LPS stimulation differences are indicated by PC1 ( Fig. 2A) macrophages and foam cells; however neonatal macrophages did not contain lipid residues [18,19]. Furthermore, a significant lack of F4/80 expression, reduced expressions of CD11b and CD14 was shown, whereas other markers of the myeloid lineage, such as CD68 were equally expressed.…”
Section: Discussionmentioning
confidence: 93%
“…2A) and 20 differentially regulated KEGG pathways; LPS stimulation differences are indicated by PC1 ( Fig. 2A) macrophages and foam cells; however neonatal macrophages did not contain lipid residues [18,19]. Furthermore, a significant lack of F4/80 expression, reduced expressions of CD11b and CD14 was shown, whereas other markers of the myeloid lineage, such as CD68 were equally expressed.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, these lipid-laden foam cells, present from the earliest discernable fatty streak lesions to advanced complicated lesions and plaque disruption, are key regulators of the pathological behavior of plaques [1][2][3][4][5]47) . Hence, reducing the formation of foam cells may be an efficient strategy for treating and preventing atherosclerosis 4) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, excessive lipid accumulation in macrophages of the arterial intima drives the secretion of proinflammatory mediators, potentiating atherogenesis 3) . Lipid homeostasis, particularly cholesterol homeostasis, is a critical step in the formation of macrophage foam cells 4,5) . Macrophage cholesterol homeostasis maintenance is generally thought to result from the balance between influx, endogenous synthesis/hydrolysis, and efflux.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of foam cells within the arterial wall is thought to play a pivotal role in the development of atherosclerotic lesions (24). In the last decade, several studies have shown that in addition to macrophages, VSMCs accumulate excess intracellular cholesteryl (25,26) and give rise to a significant number of foam cells in atherosclerotic lesions (14,27).…”
Section: Discussionmentioning
confidence: 99%